KONSEP NITU DALAM KEPERCAYAAN MASYARAKAT DUSUN LEWOURAN - Muda, Stefanus Dama; Muda, Florianus Pruda (Studi Budaya Nusantara, 2024)
This article explores the concept of nitu (spirit) in the beliefs of the Lewouran village community, located in LewotobiSubdistrict, East Flores Regency, East Nusa Tenggara. Specifically, it delves into the concept of nitu in the traditional beliefs of the Lewouran community. The objective of this article is to elucidate whether nitu indeed possesses distinct powers in the lives of the Lewouran villagers. The research employs a qualitative descriptive methodology, combining field research and literature review methods. The findings of this study suggest that nitu, especially nitu date (malevolent spirit), are not merely individual or collective spiritual entities with specific supernatural abilities. Instead, they can have a significant impact on human life, leading to illnesses, diseases, and various calamities within the community.